PENGEMBANGAN SISTEM INFORMASI STOK BARANG PADA TOKO MATRIX KOMPUTER - Muhammad Jibril; Muhammad Amin (Indragiri Islamic University, 2022)
A sales store on a large scale must have a lot of processing regarding inventory data. Fast and accurate handling is needed considering that the amount of inventory is not small. To help reduce errors and speed up data processing, a computer is needed. With this tool, it is hoped that a sales store can take the benefits and apply it to the store so that it is easy to get information about the data of goods at that time. The purpose of this paper is to create an inventory information system so that daily activities can run smoothly. The data collection method used to obtain data is to use field studies and literature studies carried out with a library research process that is adequate, supportive and relevant to these problems. With computerization, the processing of data entry, inventory, and expenditure of goods, as well as the calculation of the number of goods that have been issued can be faster and the possibility of errors is very small, the time required is also more efficient.